Blood–Brain Barrier Disruption Is Not Associated With Disease Aggressiveness in Amyotrophic Lateral Sclerosis - Prell, Tino; Vlad, Benjamin; Gaur, Nayana; Stubendorff, Beatrice; Grosskreutz, Julian (Frontiers in Neuroscience, 2021)
The pathogenesis of the fatal neurodegenerative condition Amyotrophic Lateral Sclerosis (ALS) remains to be fully understood. Blood-brain barrier damage (BBBD) has been implicated as an exacerbating factor in several neurodegenerative conditions, including ALS. Therefore, this cross-sectional study used the novel D50 progression model to assess the clinical relevance of BBBD within a cohort of individuals with either ALS (n = 160) or ALS mimicking conditions (n = 31). Routine laboratory parameters in CSF and blood were measured and the ratio of CSF to serum albumin levels (Qalb) was used as a proxy measure of BBBD. In the univariate analyses Qalb levels correlated weakly with disease aggressiveness (as indicated by individual D50 values) and the physical function (as measured by ALS-Functional rating scale). However, after adjustment for cofactors in the elastic net regularization, only having limb-onset disease was associated with BBBD. The results reported here emphasize the clinical heterogeneity of ALS and the need for additional longitudinal and multi-modal studies to fully clarify the extent and effect of BBBD in ALS.